Modalities and specificities of financing social enterprises - Barjaktarović Miljana; Jovanović Dražen; Petković Biljana (Trendovi u Poslovanju)
This paper presents modalities and instruments of financing social enterpreneurship which solve problems in the business of social enterprises and at the same time influence and contribute to the development of society. The survival, growth and development of these enterprises is their primary characteristic and the problem mostly determined by sources of their financing, their price and other conditions of use. Grants, micro credits, social bonds, hybrid financing, mezzanine financing, crowfunding are just some of the instruments available to social enterprises in the countries of the region, and the biggest support for their application comes from the European Union funds.